Determinants of the technological intensity of state exports for the period of rising commodity prices - Teixeira, Felipe Orsolin; Coronel, Daniel Arruda; Oreiro, José Luis da Costa (Brazilian Journal of Political Economy, 2021)
The aim of this paper is to analyze the behavior and determinants of Brazilian states exports, by technological intensity levels, for the period of commodity prices shocks. The results showed that sectors of higher technology lost representativeness in exports and that the real exchange rate can facilitate access for strategic sectors in the international market. JEL Classification: F43; R11; C23.